A 3-Year Review of an Outpatient Burn Sedation Program in a Tertiary Burn Care Centre: Is It Safe and Does It Work?. Issue 4 (November 2019) - Chan, Rayleigh; Van Slyke, Aaron C.; Bucevska, Marija; Verchere, Cynthia
Introduction: The burn treatment room at our tertiary-care centre is run by a multidisciplinary team, providing care to primarily burn patients who require moderate to deep sedation to undergo dressing changes in a monitored setting outside the operating room. There is little literature on the safety, efficacy, and logistics of treating outpatient pediatric burn patients in this manner. This study reviews the safety of deep sedation in the burn treatment room. Methods: A retrospective chart review of patients with burns treated in the burn treatment room from 2013 to 2015 was conducted. Patient demographics, diagnosis, procedure details, sedation, and adverse events were recorded. Data were analyzed descriptively. Results: Sevety-four patients with burns had a total of 308 visits in the burn treatment room for burn bath and/or dressing changes. Scald burns were the most common mechanism of injury (n = 56). Most burns were superficial and mid-dermal (54%), initially estimated at 5% to 10% TBSA (50%). Of the 308 visits, 304 required sedation. Adverse events were recorded in 11 (3.6%) of 304 sedated procedures. None of these events were critical: 7 patients required intravenous conversion due to inadequate oral sedation, 2 experienced brief apnea episodes but recovered spontaneously, and 2 had delayed discharge of more than 2 hours due to residual sedation. Conclusion: The burn treatment room is a safe and effective setting for treating pediatric burn patients, bypassing what might historically require operating suite inpatient management.